2015
DOI: 10.1186/s12934-015-0348-8
|View full text |Cite
|
Sign up to set email alerts
|

A particular silent codon exchange in a recombinant gene greatly influences host cell metabolic activity

Abstract: BackgroundRecombinant protein production using Escherichia coli as expression host is highly efficient, however, it also induces strong host cell metabolic burden. Energy and biomass precursors are withdrawn from the host’s metabolism as they are required for plasmid replication, heterologous gene expression and protein production. Rare codons in a heterologous gene may be a further drawback. This study aims to investigate the influence of particular silent codon exchanges within a heterologous gene on host ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 62 publications
1
27
0
Order By: Relevance
“…After an initial exponential increase, the OTR of BL21(DE3), Rosetta(DE3), and HMS174(DE3) decreases slightly for several hours (Figure A, B, and C). This phase is typically associated with recombinant protein production . Afterward, the OTR increases again, which is indicative for a second noninduced growth phase .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…After an initial exponential increase, the OTR of BL21(DE3), Rosetta(DE3), and HMS174(DE3) decreases slightly for several hours (Figure A, B, and C). This phase is typically associated with recombinant protein production . Afterward, the OTR increases again, which is indicative for a second noninduced growth phase .…”
Section: Resultsmentioning
confidence: 96%
“…In their work, a correlation between OTR reflecting the metabolic state of the culture and recombinant protein production was observed. In addition, Rahmen et al confirmed these findings for E. coli BL21(DE3) clones expressing identical proteins only differing in a single amino acid or a single codon of the heterologous protein …”
Section: Introductionmentioning
confidence: 81%
“…The phenomenon of a more or less constant OTR after induction is well known from auto‐induction media containing glucose, lactose, and glycerol. Several studies identified a phase of rather constant OTR after induction with IPTG or its analogue lactose as production phase and indication of the strength of metabolic burden . An equivalent behavior is shown here for the first time in a mineral medium using arabinose as inducer.…”
Section: Resultsmentioning
confidence: 54%
“…But considering different well geometries and shaking parameters, the resulting increased maximum oxygen transfer capacities can be comparable to stirred tank systems [3032]. Based on the literature [16, 28, 33, 34], all cultivations of this section are expected to be oxygen unlimited.…”
Section: Resultsmentioning
confidence: 99%
“…The OTR provides important information about growth behavior and metabolism, it enables mass balancing and evaluation of stoichiometric relationships for aerobic cultivations [1215]. Even estimations about the product formation are possible on the basis of the OTR [16, 17]. According to the state of the art, the OTR is determined via off gas analytics in fermenter scale [18].…”
Section: Introductionmentioning
confidence: 99%